Clinical Features and Management of Chronic Abdominal Pain Syndrome in Children: A Multifactorial Approach (International journal of artificial intelligence, 2026)
Chronic abdominal pain syndrome (CAPS) in children is common, disabling, and largely functional in origin. It arises from the interaction of biological factors (visceral hypersensitivity, altered motility, mucosal immune activation, microbiota changes), psychological factors (anxiety, depression, stress reactivity), and social factors (family responses, school stressors), within the framework of disorders of gut–brain interaction. This article reviews clinical presentation, red flags and differential diagnosis, practical evaluation strategies that minimize unnecessary testing, and evidence-informed management emphasizing a biopsychosocial model. Multimodal treatment—education and reassurance, graded return to function, targeted dietary measures, microbiota modulation, psychological therapies (CBT, gut-directed hypnotherapy), and judicious pharmacotherapy—improves symptoms and quality of life while reducing health-care utilization.